PENDAMPINGAN MASYARAKAT DESA KEPANJEN, KABUPATEN JEMBER DALAM PENGOLAHAN LAHAN SALIN UNTUK SISTEM TANAM TUMPANGSARI - Nur Khozin, Mohammad; Bintaro, Jatmiko Hardi; Soeparjono, Sigit; Putri, Widya Kristiyanti (PAPUMA: Journal of Community Services, 2023)
Marginal land in Indonesia is one of the prospects for developing productive agricultural areas. One of the marginal lands is saline land located in Mayangan Village, Gumukmas District, Jember Regency. The saline land in this area tends to be sandy and difficult to retain water. The aim of this service is to provide information and experience for farmers about how to cultivate saline land. The service activities carried out by the Ecophysiology research group are in the form of assistance to the community in 2 stages, namely socialization of land processing using organic materials and implementation of an intercropping system for corn and peanuts. The service was carried out for 5 months. This activity was attended by farmer group in Mayangan Village. The result of the service is an increase in the community's ability to process saline land into more productive land.